Muzyczne harmonie i harmonia świata. „Pieśni Ziemi i Mocy” Grega Beara - Joanna Kokot (Literatura i Kultura Popularna)
One of the main themes of Greg Bear’s dylogy, Songs of Earth and Power is music (as well as art in general) and its power to change the material reality. The multiverse is presented there as analogous to a musical piece, however — contrary to ancient and medieval concepts — it is not a finished opus, but one that undergoes contiguous change, becoming more and more intricate in the process. The paper explores the relation between music and magic, or rather between art and magic, artistic works being the eponymous songs of power, as well as the meaning of music as it is interpreted in Bear’s dylogy.